ASSESSMENT OF FEMALE MARRIED STAFF HEALTH LITERACY TOWARDS REPRODUCTIVE HEALTH BEHAVIOUR AT THE UNIVERSITY OF IBADAN, NIGERIA (Journal of the Management Sciences, 2025)
Health literacy is a potent factor that determines several health-related variables including reproductive health. The study assessed health literacy and its relationship with reproductive health behaviour among female staff at the University of Ibadan, Nigeria. The cross-sectional study was performed in 2024 on 185 female staff of the University of Ibadan aged between 19 to 49 years who had been selected through a stratified and random sampling technique from among those with the criteria for entering the study. Two adapted instruments labelled Health Literacy (α=0.79) and Reproductive Health Behaviour Questionnaires (α=0.81) were used for data collection and analysed using frequency counts, percentages and Pearson Product Moment Correlation at a significant level of less than 0.05. The study found that the average mean health literacy of female employees at the University was high (x ̅=3.89., there is a significant relationship between health literacy and reproductive health behaviour among female staff at the University(r=.504 p
Keywords: Health Literacy; Reproductive Health Behaviour; Female Married Staff; University